Risk of Uterine Rupture during Labor among Women with a Prior Cesarean Delivery - Mona T. Lydon‐Rochelle; Victoria L. Holt; Thomas R. Easterling; Diane P. Martin (2001)
Each year in the United States, approximately 60 percent of women with a prior cesarean delivery who become pregnant again attempt labor. Concern persists that a trial of labor may increase the risk of uterine rupture, an uncommon but serious obstetrical complication.